Vers un journalisme réifié ? - Faïza Naït-Bouda (Communication)
This article analyzes how the exclusion of freelance journalists from the core group of legitimate French journalists during the inter-war period can be interpreted as being simultaneously an indicator and a result of the social logic of reification of both journalism and journalists. With the benefit of almost a century of hindsight, the author examines the historical branding of freelance journalists as illegitimate and challenges the argument that this branding was the sole workings and result of the reification of legitimate journalism and journalistic practices, whose genesis and effects extended far beyond the perimeters of this profession.